Grain yield loss and seed nutritional quality alteration in faba bean (Vicia faba L.) caused by the stem borer Lixus algirus L. (Coleoptera: Curculionidae) - Ouaarous, Mohamed; Choukri, Hasnae; Tika, Asma; Amri, Moez; Baouchi, Adil; Ramdani, Chaimae; Taadaouit, Nezha Ait; Boulamtat, Rachid; Meftah Kadmiri, Issam; Aasfar, Abderrahim; Sobeh, Mansour; Drissi, BadrEddine; et al. (Frontiers in Insect Science, 2025)
Faba bean (Vicia faba L.) is one of the most important cool-season legume crops worldwide, particularly in the Mediterranean regions. It plays a crucial role in cereal-based crop rotations and serves as an accessible and cost-effective protein source for both human diets and livestock feed. Despite its significance, faba bean production is heavily impacted by the stem borer Lixus algirus L. (Coleoptera: Curculionoidea), a prominent insect pest in the Mediterranean region. This research aimed to assess the impact of L. algirus on grain yield and seed nutritional profile of a local variety ‘Defes’. The experiment was conducted using insect-proof cages at ICARDA - Marchouch research station during the 2018–2019 and 2019–2020 seasons. The findings revealed that L. algirus infestation caused grain yield losses ranging from 14% to 20%. Larval feeding within plant stems significantly altered seed nutritional composition compared to seeds from non-infested plant, ICP-OES analysis revealed significant declines were observed in magnesium (44%), manganese (38%), calcium (37%), zinc (30%), and iron (27%) concentrations in seeds collected from infested plants. In contrast, an increase in seed protein content and total sugar levels was recorded in infested plant seeds compared to non-infested plants. Similar results were observed for both essential amino acids (such as threonine, isoleucine, leucine, phenylalanine, histidine, lysine, and arginine) and non-essential amino acids (including glutamic acid, tyrosine, and alanine). Multivariate analyses, including PCA and correlation, revealed distinct nutrient and morphological trait patterns between infested and non-infested faba bean samples across both seasons. Collectively, these results show that L. algirus not only reduces grain yield but also reconfigures seed nutritional quality, lowering mineral density despite higher protein and sugars, highlighting the need for integrating host plant resistance for stem borer management and timely IPM to preserve both productivity and food/feed quality.